2013
DOI: 10.1177/0193945913480429
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and Barriers to Participating in Health Promotion Behaviors in Black Men

Abstract: There is limited research examining the health promotion behaviors (HPBs) of low-income Black men. This study examined the relationship between HPBs, and motivators and barriers to participating in these behaviors in Black men (N = 107), aged 21 to 56. Using descriptive statistics, more than 96% of the participants reported they were motivated because of the desire to be healthy. Canonical correlation analysis and conditional random forest were used to determine the importance of individual motivators and barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…As was found in prior research conducted with rural communities 29,32,37,38 , pastors and similar church leaders, by virtue of their position, were respected authority figures in the community. Thus, pastors’ involvement and education on the topic would increase congregants’ trust in HPV vaccine uptake information being disseminated by educators and their desire to get more information to make informed decisions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…As was found in prior research conducted with rural communities 29,32,37,38 , pastors and similar church leaders, by virtue of their position, were respected authority figures in the community. Thus, pastors’ involvement and education on the topic would increase congregants’ trust in HPV vaccine uptake information being disseminated by educators and their desire to get more information to make informed decisions.…”
Section: Discussionsupporting
confidence: 51%
“…Church-based health promotion interventions have been noted for their ability to reach broad populations and their potential for influencing members’ behaviors at multiple levels of change. 28,29,31,32 DeHaven et al (2004) examined the published literature on health programs in faith-based organizations to determine the effectiveness of these programs. They found that across all types of illness or health concerns, faith-based programs contributed to improved health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, 66.1% of all new HIV diagnoses in NYC were among black men, of which 56.2% were MSM(NYCDOHMH, 2012). Compared to other racial-ethnic groups, HIV-infected BMSM are less likely to know their HIV status (Centers for Disease Control and Prevention (CDC), 2005; MacKellar et al, 2005; Millett, Peterson, Wolitski, & Stall, 2006) and have lower rates of retention in HIV care (Calvert & Isaac-Savage, 2013; Christopoulos, Das, & Colfax, 2011; Giordano, Hartman, Gifford, Backus, & Morgan, 2009); they are less likely to be virally suppressed than HIV-infected White MSM (Beer, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Being too busy and lack of time have been reported as primary barriers for eating healthy (DiSantis et al, 2013;Hargreaves et al, 2002;Lucan, Barag, Karasz, Palmer, & Long, 2012;Sigrist, Anderson, & Auld, 2005;Welsh et al, 2012). Other barriers reported among adult populations in the literature include lack of knowledge (e.g., not sure what to eat), lack of social support, sense of social isolation, competing family responsibilities, motivation, lack of control, non-availability of healthy food options, transportation, cost, dislike of cooking, food preferences, social and cultural symbolism of certain foods, taste, poor oral health, confusing messages from the media/research, lack of cooking skills, and eating healthy not being a priority (Abbott, Davison, Moore, & Rubinstein, 2010;AbuSabha & Achterberg, 1997;Brug, 2008;Calvert & Isaac-Savage, 2013;DiSantis et al, 2013;Hargreaves et al, 2002;James, 2004;Kumanyika, 2007;Lucan et al, 2012;Nicklas et al, 2013;Pawlak & Colby, 2009;Sigrist et al, 2005;Timmerman, 2007;Walcott-McQuigg, 1995;Welsh et al, 2012).…”
Section: Perceived Barriers For Healthy Eating and Dfimentioning
confidence: 99%